Task Allocation and Corporate Performance: Is There a First-Mover Advantage? - Michael Beckmann; Kathrin Armbruster; Dieter Kuhn (University of Basel, Center of Business and Economics (WWZ), 2012)
Although the performance effects of multitasking were analyzed intensively in the past, little is known about the impact of the adoption time of multitasking on corporate performance. Possibly, the quantity of the reorganization is crucial and early movers experience a comparative competitive advantage; but also quality effects could dominate and late adoption is beneficial. The present paper examines the performance effects of the implementation time of teamwork and job rotation using two nationally representative Swiss firm-level datasets. To account for potential endogeneity, two separate two-stage estimation strategies are applied. According to the results, there are slight late-mover disadvantages when implementing teamwork. In contrast, the influence of the adoption of job rotation heavily depends on the observation time, though late adoption is mainly associated with lower performance. These findings indicate that there are both quantity and quality effects, dependent on how established and complex the multitasking instrument is.
Keywords: C21; C24; D24; M12; 330; Task Allocation; First Mover; Late Adopter; Firm Performance; Switzerland; Arbeitsgruppe; Organisatorischer Wandel; Erfolgsfaktor; Performance-Messung; Unternehmensorganisation; Schweiz